Cutaneous Lipomatous Metaplasia in Patient with Severe Atopic Dermatitis in Therapy with Dupilumab - Ferrucci, Silvia Mariel; Angileri, Luisa; Tavecchio, Simona; Berti, Emilio; Parafioriti, Antonina; Boggio, Francesca; Boneschi, Vinicio (Archives of Clinical and Biomedical Research, 2022)
Introduction: Lipomatous Metaplasia (LM) is a well-known aspect associated to a variety of inflammatory and neoplastic processes. Case presentation: Here, we describe a case of LM arising in a woman during dupilumab treatment. To our knowledge there are no data in the literature about side effects similar to the clinical picture we observed in our patient. Conclusion: We have supposed that inhibition of IL-4, together with chronic photo-exposure, could have induced the development of mature fatty tissue in the context of a cytokine pattern modified by therapy with dupilumab.